Access to and interest in human milk research opportunities among Black pregnant and postpartum people - Asiodu, Ifeyinwa V.; Gay, Caryl L.; Gates-Burgess, Brandi; Negrete, Gabriela (Frontiers in Nutrition, 2024)
Background: Concerns exist regarding biomedical research participation in marginalized and historically disadvantaged communities.The purpose of this study was to understand critical barriers to participation in human milk research from the perspective of Black pregnant and postpartum people.: A national sample of Black pregnant and postpartum people (n=104) was recruited to complete a cross-sectional online survey informed by the Life Course Perspective. Survey questions assessed research experiences and preferences, particularly related to human milk research, knowledge of historical events/policies targeting Black communities, and demographic characteristics. A socio-economic composite score was calculated as an indicator of socioeconomic advantage. Survey data were summarized descriptively and potential correlates of research engagement were evaluated.Results: Most (69%, n=71) respondents reported previous participation in a research study, yet only 8 (8%) reported ever being asked to participate in a breastfeeding/chestfeeding or human milk study, and one respondent was unsure. Despite so few having been asked, 59% (n=61) of respondents indicated they would donate breast/human milk to research if asked. Respondent characteristics associated with prior research participation included having greater socioeconomic advantage (p=.027) and greater knowledge of discriminatory historical events/policies (p<.001). In contrast, the only respondent characteristic associated with willingness to donate human milk to research was younger age (p=.002).: Our findings suggest that Black pregnant and postpartum people are interested in biomedical research, specifically human milk and lactation research. However, greater intentionality and targeted recruitment of this underrepresented population is needed to increase diversity among human milk and lactation study samples.barriers related to access and engagement may be hindering efforts to increase participation in human milk research among this underrepresented populatio n. Structural and community-based interventions, informed by community members, are needed to address concerns and improve participant engagement.* The socio-economic composite is the count of 4 socio-economic indicators (college education, employment, private insurance, and income >$50,000/year) and excludes the 6 participants who did not report an income. ** Knowledge scores ranged from 1="Not at all knowledgeable" to 5="Most knowledgeable (expert)"